Systematic Literature Review: Performance & Development of Creative Economy-Based MSMEs - Zidane, Muhammad Raihan; Nawawi, Zuhrinal M; Tambunan, Khairina (Moneter: Jurnal Keuangan dan Perbankan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) based on the creative economy play a strategic role in driving national economic growth and creating inclusive employment opportunities. However, amid the post-pandemic economic dynamics and accelerated digital transformation, the development of creative MSMEs faces complex structural and cultural challenges. This study aims to identify key barriers and formulate effective development strategies for creative economy-based MSMEs in Indonesia. Utilizing a Systematic Literature Review (SLR) approach, this research reviews and synthesizes 42 relevant academic publications sourced from reputable databases such as Google Scholar, DOAJ, and SINTA. The analysis employed meta-synthesis and content analysis techniques to reveal thematic patterns and relationships between strategic variables. The findings indicate that the primary obstacles include limited access to financing, low levels of digital and entrepreneurial literacy, and inadequate institutional support. Meanwhile, the most effective development strategies encompass business digitalization, entrepreneurship training, multi-stakeholder collaboration, business model innovation, and policy reforms based on intellectual property rights. This study contributes conceptually by mapping thematic strategies for the development of creative MSMEs, while also offering a foundation for formulating more contextual, responsive, and sustainable empowerment policies and practices. The article is expected to serve as a vital reference for scholars, policymakers, and practitioners in promoting the sustainability and competitiveness of creative economy-based MSMEs in Indonesia.